Adaptive laboratory evolution to obtain furfural tolerant Saccharomyces cerevisiae for bioethanol production and the underlying mechanism - Yao, Lan; Jia, Youpiao; Zhang, Qingyan; Zheng, Xueyun; Yang, Haitao; Dai, Jun; Chen, Xiong (Frontiers in Microbiology, 2024)
Furfural, a main inhibitor produced during pretreatment of lignocellulose, has shown inhibitory effects on S. cerevisiae. In the present study, new strains named 12-1 with enhanced resistance to furfural were obtained through adaptive laboratory evolution, which exhibited a shortened lag phase by 36 h, and an increased ethanol conversion rate by 6.67% under 4 g/L furfural. To further explore the mechanism of enhanced furfural tolerance, ADR1_1802 mutant was constructed by CRISPR/Cas9 technology, based on whole genome re-sequencing data. The results indicated that the time when ADR1_1802 begin to grow was shortened by 20 hours compared with reference strain (S. cerevisiae CEN.PK113-5D) when furfural was 4 g/L. Additionally, the transcription levels of GRE2 and ADH6 in ADR1_ 1802 mutant were increased by 53.69% and 44.95%, respectively, according to real-time fluorescence quantitative PCR analysis. These findings suggest that the enhanced furfural tolerance of mutant is due to accelerated furfural degradation.Importance: Renewable carbon worldwide is vital to achieve "zero carbon" target.Bioethanol obtained from biomass is one of them. To make bioethanol price competitive to fossil fuel, higher ethanol yield is necessary, therefore, monosaccharide produced during biomass pretreatment should be effectively converted to ethanol by Saccharomyces cerevisiae. However, inhibitors formed by glucose or xylose oxidation could make ethanol yield lower. Thus, inhibitor tolerant Saccharomyces cerevisiae is important to this process. As one of the main component of pretreatment hydrolysate, furfural shows obvious impact on growth and ethanol production of Saccharomyces cerevisiae. To get furfural tolerant Saccharomyces cerevisiae and find the underlying mechanism, adaptive laboratory evolution and CRISPR/Cas9 technology were applied in the present study.